PRESTASI BELAJAR SISWA BERDASARKAN PERSEKTIF TEORI HUMANISTIK - Damayanti, Nola Fitria; Tasia, Anas; Maulida, Ridhna; Prahesti, Devi Tia Dewi; Rafianti, Wahdah Refia; Suriansyah, Ahmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Inequality in learning outcomes in the National Assessment at the elementary school level indicates the need for a shift from a teacher-centered approach to learning that humanizes students. This study aims to describe the application of humanistic learning theory, analyze its influence on student motivation and achievement, and synthesize relevant learning strategies. Using a literature review method, this study examines empirical articles published between 2021 and 2025 sourced from accredited scientific databases. The analysis results show that the implementation of humanistic principles, through the teacher's role as a facilitator and differentiated learning strategies, significantly increases intrinsic motivation and student academic achievement. An inclusive and supportive learning environment is proven to meet affective needs, encourage self-actualization, and reduce students' psychological barriers in learning. This study concludes that the humanistic approach is a strategic solution to address educational quality disparities and build holistic student character.